Creation of Learning Videos on Balinese Folk Song Arrangements for Junior High School Art and Culture Teachers in Buleleng Regency and Denpasar City - Ni Luh Sustiawati; Ni Wayan Ardini; I Komang Darmayuda (Institut Seni Indonesia Denpasar, 2024)
The purpose of this research is to comprehend the learning of group vocal arrangements including their forms and stages for the environment of arts and culture teachers at junior high school in Buleleng Regency and Denpasar City through making related learning videos. The research method used is qualitative and quantitative, with data collection techniques through interviews, observation, document study, discography, and questionnaire. The theory used is the theory of analysis of the form and structure of the song and the theory of function. Primary data sources were obtained from interviews, observations, and discography (VCD). Secondary data was obtained from books, journals, and internet materials. The results showed that by providing material for Balinese folk songs arrangement in group vocals at the level of junior high school teachers in Buleleng Regency and Denpasar City through a video learning process, students' interest in learning music arrangement increased and allowed them to practice directly conveying the results of the arrangement in group vowel form.